Is the proteomic composition of the salivary pellicle dependent on the substrate material?. Issue 3 (3rd March 2022) - Trautmann, Simone; Künzel, Nicolas; Fecher‐Trost, Claudia; Barghash, Ahmad; Dudek, Johanna; Flockerzi, Veit; Helms, Volkhard; Hannig, Matthias
Abstract: Purpose: The use of dental restorative materials is a routine task in clinical dentistry. Upon exposure to the oral cavity, continuous adsorption of salivary proteins and other macromolecules to all surfaces occurs, representing the first step in dental biofilm formation. Different physico‐chemical properties of substrate materials potentially influence the composition of the initial biofilm, termed pellicle. This study aimed at characterizing and comparing the individual proteomic composition of the 3‐min pellicle formed on bovine enamel and six restorative materials. Experimental Design: After chemical elution, pellicle proteins were identified by nano‐LC‐HR‐MS/MS. Proteomic profiles were analyzed in terms of molecular weights, isoelectric points, molecular functions and compared to saliva to reveal substrate material‐specific adsorption patterns. Results: A total of 1348 different pellicle proteins were identified, with 187–686 proteins in individual 3‐min pellicles. Unexpectedly, this yielded quite similar distribution patterns independent of the substrate materials. Furthermore, overall similar fold changes were obtained for the major part of commonly enriched or depleted proteins in the pellicles. Conclusions and Clinical Relevance: The current results point to a minor role of the substrate material on the proteomic composition of the 3‐min pellicle and represent core data for understanding the complex surface interactions in the oral cavity.